A spontaneous gravity prior: newborn chicks prefer stimuli that move against gravity. (8th February 2023) - Bliss, Larry; Vasas, Vera; Freeland, Laura; Roach, Robyn; Ferrè, Elisa Raffaella; Versace, Elisabetta
Abstract : At the beginning of life, inexperienced animals use evolutionary-given preferences (predispositions) to decide what stimuli to attend and approach. Stimuli that contain cues of animacy, such as face-like stimuli, biological motion and changes in speed, are particularly attractive across vertebrate taxa. A strong cue of animacy is upward movement against terrestrial gravity, because only animate objects consistently move upward. To test whether upward movement is spontaneously considered attractive already at birth, we tested the early preferences of dark-hatched chicks ( Gallus gallus ) for upward- versus downward-moving visual stimuli. We found that, without any previous visual experience, chicks consistently exhibited a preference to approach stimuli that move upward, against gravity. A control experiment showed that these preferences are not driven by avoidance of downward stimuli. These results show that newborn animals have a gravity prior that attracts them toward upward movement. Movement against gravity can be used as a cue of animacy to orient early approach responses in the absence of previous visual experience.